Determinan Kejadian Tuberkulosis pada Orang dengan HIV/AIDS - Muna, Ni'mal; Cahyati, Widya Hary (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2019)
ABSTRACT Tuberculosis and HIV/AIDS infection has a very strong relationship, and with the presence of HIV infection the insidence of TB disease is increasing. The purpose of this study is to determine the incidence of TB in people with HIV/AIDS health services in Semarang. The type of this research is analytic observational with case-control research design to know the determinant of tuberculosis in people with HIV/AIDS. The research use secondary and primary data. The sample is determined by 30 cases and 30 controls. The instrument use a questionnaire. Data analyzed by univariate analysis to describe caharacteristics and bivariate analysis. The results obtained from factors correlation with incidence of tuberculosis in people with HIV/AIDS are smoking history (p-value = 0,002; OR= 19,33; 95% CI: 2.313-161.565), clinical stage HIV (p-value =0,000; OR=0,067; 95% CI: 0,017-0,254), history of contact with TB patients ( p-value = 0,001; OR=8; 95% CI:2,475-25,860 ). Suggestions obtained from this study are to reduce smoking actvities, always monitor the condition of the body and routine follow the treatmen and wear maskd to reduce the risk of contact with TB patients. Kerwords: Opportunistic Infections, HIV/AIDS, Tuberculosis.